(untitled) (Baghdad Science Journal, 2007)
Five representative sampling stations were selected in upper region of Euphrates river. Bimonthly sampling were collected from December 2000 to December 2001. Rotifera showed high density in December 2000 while high density of cladocera which recorded in October .The results of relative abundance index showed that rotifera: Polyarthera dolichoptera , Keratella cochlearis , K. valga, Cephalodella auriculata and cladocera: Bosmina longirostris , B.coregoni ,Chydorus spharicus, were more abundant in study stations. The results of constancy index showed 4 taxa belonged to rotifera and 2 taxa belonged to cladocera which were considered constant in the Euphrates river, where the other species varied between accessory and accidental species in study stations. The index values of Species richness of rotifera varied between 0.41 – 2.8 and cladocera varied between 0.5 - 1.95. The Shanon-Weiner index of rotifera varied between 0.54-1.72 bit/ind., while the Shanon index of cladocera varied between 0.5-1.6 bit/ind. The uniformity index of rotifera varied between 0.41 – 0.99 but the uniformity index of cladocera varied between 0.61- 0.98 .